Arachidonic Acid Derivatives and Neuroinflammation - Gorica, Era; Calderone, Vincenzo (CNS & Neurological Disorders - Drug Targets, 2022)
Neuroinflammation is characterized by dysregulated inflammatory responses localized within the brain and spinal cord. Neuroinflammation plays a pivotal role in the onset of several neurodegenerative disorders and is considered a typical feature of these disorders. Microglia perform primary immune surveillance and macrophage-like activities within the central nervous system. Activated microglia are predominant players in the central nervous system response to damage related to stroke, trauma, and infection. Moreover, microglial activation per se leads to a proinflammatory response and oxidative stress. During the release of cytokines and chemokines, cyclooxygenases and phospholipase A2 are stimulated. Elevated levels of these compounds play a significant role in immune cell recruitment into the brain. Cyclic phospholipase A2 plays a fundamental role in the production of prostaglandins by releasing arachidonic acid. In turn, arachidonic acid is biotransformed through different routes into several mediators that are endowed with pivotal roles in the regulation of inflammatory processes. Some experimental models of neuroinflammation exhibit an increase in cyclic phospholipase A2, leukotrienes, and prostaglandins such as prostaglandin E2, prostaglandin D2, or prostacyclin. However, findings on the role of the prostacyclin receptors have revealed that their signalling suppresses Th2-mediated inflammatory responses. In addition, other in vitro evidence suggests that prostaglandin E2 may inhibit the production of some inflammatory cytokines, attenuating inflammatory events such as mast cell degranulation or inflammatory leukotriene production. Based on these conflicting experimental data, the role of arachidonic acid derivatives in neuroinflammation remains a challenging issue.
Keywords: Neuroinflammation